THE ETHICS OF DUTY IN IBN MISKAWAIH'S THOUGHT: AN ANALYSIS OF INDIVIDUAL RESPONSIBILITY IN SOCIETY - Yolanda, Legin (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2024)
Abstract: Every individual certainly has obligations and responsibilities in social life. Ibn Miskawaih is a philosopher who is called the father of Islamic ethical philosophy. In ethics, the obligation emphasizes how each individual obeys, adheres to, and carries out his responsibilities as part of the social community The purpose of this research is to examine Ibn Miskawaih's ethical obligations and find out what individual responsibilities are in society. Through a qualitative approach, this research uses library research and text analysis methods to obtain in-depth information about Ibn Miskawaih's ethical thoughts and individual responsibility in society. The results of this research show that an ethic of obligation can encourage every individual to carry out their obligations or responsibilities in society.